Detection of secondary and backscattered electrons for 3D imaging with multi-detector method in VP/ESEM. (January 2018) - Slówko, Witold; Wiatrowski, Artur; Krysztof, Michał
Highlights: Problems of adaptation of the multi-detector method for 3D imaging are described. Problems of 3D imaging of wet bio-medical samples are discussed. The Pressure Limiting Aperture was used as the signal collector. Mechanisms of the detectors operation have been illustrated with computer simulations. Abstract: The paper considers some major problems of adapting the multi-detector method for three-dimensional (3D) imaging of wet bio-medical samples in Variable Pressure/Environmental Scanning Electron Microscope (VP/ESEM). The described method pertains to "single-view techniques", which to create the 3D surface model utilise a sequence of 2D SEM images captured from a single view point (along the electron beam axis) but illuminated from four directions. The basis of the method and requirements resulting from them are given for the detector systems of secondary (SE) and backscattered electrons (BSE), as well as designs of the systems which could work in variable conditions. The problems of SE detection with application of the Pressure Limiting Aperture (PLA) as the signal collector are discussed with respect to secondary electron backscattering by a gaseous environment. However, the authors' attention is turned mainly to the directional BSE detection, realized in two ways. The high take off angle BSE were captured through PLA with use of the quadruple semiconductor detector placed inside the intermediate chamber, while BSE starting at lower angles were detected by the four-folded ionization device working in the sample chamber environment. The latter relied on a conversion of highly energetic BSE into low energetic SE generated on walls and a gaseous environment of the deep discharge gap oriented along the BSE velocity direction. The converted BSE signal was amplified in an ionising avalanche developed in the electric field arranged transversally to the gap. The detector system operation is illustrated with numerous computer simulations and examples of experiments and 3D images. The latter were conducted in a JSM 840 microscope with its combined detector-vacuum equipment which could extend capabilities of this high vacuum instrument toward elevated pressures (over 1 kPa) and environmental conditions.